COMPARISON OF THE DIETETIC AND ANTHROPOMETRIC PROFILE OF HANDBALL ATHLETES DURING A TRAINING PERIOD (Fiep Bulletin - online, 2012)
In spite of the increasing participation of females in competitive sports and of the advances in medicine and sports nutrition, there are not many studies about nutritional aspects which are specific to that population yet. Therefore, this paper aimed to compare the dietetic and anthropometric profile of female handball athletes during two distinct stages, in the pre-training (beginning of the season) and post-training (after four months training) period. Sixteen female athletes from a handball team were assessed. The methods used were: three-day food journal and verification of anthropometric measures, such as weight, height and skin folds. Analyzing the food consumption of three days, it was found, in the pre-training period an average consumption of 1883,41Kcal, 284,35g of carbohydrates, 74,82g of proteins and 25,74% of lipids. In the post-training period, however, the average consumption was of 2101,62Kcal, 280,55g of carbohydrates, 83,64g of proteins and 32,74% lipids. Regarding hydric intake, we verified that the consumption was below recommended, the athletes' average being 1,78Lts a day. Body fat percentage found was 23,2 % (± 3,2) and 22,4% (± 2,8) in the first and second collection respectively, and fat-free mass average was 47,91Kg (± 4,7) in pre-training and 49,28Kg (± 5,3) in post-training period. One concludes that the athletes' body fat percentage decreased after four months of training and there was an increase in fat-free mass. There was a significant difference in the handball athletes' feeding habits, in the different stages of training, and food consumption was inadequate regarding calories, macronutrients and hydric intake, if comparing it with the reference consumption. Therefore, this study enhances the need for more nutritional information and for monitoring of the athletes by a professional in the field of nutrition to the optimization of their performance during trainings and competitions.
Keywords: Handball; Macronutrients; Body Fat Percentage.